Guarantee the working right of people with disabilities post-covid 19 in Vietnam now - Nguyen, Thi Thu Ha (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The political report of the 12th Central Committee of the Communist Party of Vietnam at the 13th National Congress of the Communist Party of Vietnam has set out the development orientation of the country from 2021 to 2030. There is the task of "Paying attention to all people, ensuring labor, employment, and income policies, well implementing social welfare and social security. Improving the material and spiritual life of the people"; "Develop a comprehensive social security system, towards universal coverage with policies to prevent, reduce and overcome risks for the people, ensuring support for disadvantaged groups". These are the basic guiding viewpoints for central and local agencies and organizations to put in place social policies, including ensuring the rights of disadvantaged groups. The Covid-19 pandemic has had a significant impact on all aspects of social life. People with disabilities are a group of people affected by the pandemic, and the rate of people with disabilities losing their jobs or not having jobs increases. This problem requires a combination of synchronous solutions, including breakthrough policies to ensure the basic rights of people with disabilities, including the right to employment.